T HELPER 17 (Th17) AND REGULATORY T (Treg) CELLS PROFILE IN TYPE-2 DIABETES MELLITUS (T2DM) - DWIKARJANTI, INDRANITA; KRISNAMURTI, DESAK GEDE BUDI; KODARIAH, RIA (BIOMA : Jurnal Ilmiah Biologi, 2025)
One of metabolic disorder disease is Type 2 Diabetes mellitus (DM), leading to increased glucose, cholesterol, and lipid levels in the blood. Type 2 DM results in insulin resistance within the body. Glycolysis, oxidative phosphorylation, and fatty acid are the three main metabolic pathways which provide energy for T cells. T cells will ploriferate, differentiate and become active into T Helper-17 and T regulator (Treg) cells because of these pathways. The profile of TH-17 cells and Treg cells in type 2 diabetes will be opposite in terms of the number of their populations caused by metabolic disorders in the body. Type 2 diabetes make an immunology response with increasingly number of TH-17 cells, while lack of Treg cells. Many studies have shown that diabetes mellitus as a metabolic disease effect populations of T Helper-17 and regulatory T cells. Glycolysis is the main energy metabolism becomes important factor that stimulate the proliferation and differentiation of Th-17 cells. The energy produced from this metabolism is in the form of ATP, which is the result of glucose synthesis using the Glucose transporter (GLUT). Glucose transporters (GLUT-1) are most dominantly expressed by Th-17 cells and Treg cells. Metabolic disorder causes an imbalance in the population of TH-17 cells with Treg cells. This review will explain the profiles of TH-17 and regulatory T cells in Diabetes mellitus and their relationship with body metabolism disease.